Umysł ucieleśniony – haptyczność w filozofii Berkeleya - Michalski, Rafał Andrzej (Humaniora. Czasopismo Internetowe, 2024)
In this article, I aim to demonstrate that G. Berkeley’s immaterialism is founded on the concept of an embodied mind that extends into the realm of sensory experience. On the level of theological discourse, Berkeley also employs the category of the soul as an inextensible, atemporal substance. However, this metaphysical approach serves as a necessary assumption that, while completing the theoretical framework, does not play a significant role in psychological analysis. The second purpose of my interpretation is to substantiate the thesis that the sense of touch is the basis of the soul’s activity and delineates the limits of its accessible experience.